Evaluation of Carbon-11 Labelled Phenylglycine and Phenylalanine for Pancreas Scintigraphy - Vaalburg, W.; Beerling-van der Molen, H. D.; Woldring, M. G. (Nuklearmedizin - NuclearMedicine, 1975)
Carbon-11 (t½ = 20.4 min, β+) labelled DL-α-phenylalanine and DL-α-phenylglycine were administered intravenously to rats and the distribution of the radioactive amino acids over pancreas, liver, spleen, kidneys and blood was measured after several time intervals. From these results the ratios of the concentration in pancreas and liver were calculated and compared with the corresponding ratios from the literature for some 18F-labelled aromatic amino acids and L-selenomethionine-75Se. On the basis of this study it appears that DL-α-phenylglycine-l-11C, in spite of a small percentage of the administered dose reaching the pancreas, and DL-α-phenylalanine-l-11C are better suited to pancreas scintigraphy than L-selenomethionine-75Se.